A computational study on the effect of fracture intrusion distance in three‐ and four‐part trochanteric fractures treated with Gamma nail and sliding hip screw. Issue 1 (10th October 2013) - Goffin, Jérôme M.; Pankaj, Pankaj; Simpson, A. Hamish
ABSTRACT Using finite element analysis, the behaviors of the Gamma nail and the sliding hip screw (SHS) were compared in an osteoporotic bone model for the fixation of three‐ and four‐part trochanteric fractures (31‐A2 in the AO classification, types IV and V in Evans' classification). The size of the medial fragment was varied based on clinical data, and the case of a fractured greater trochanter was also considered. Our results showed that for Evans' type V stabilized with a Gamma nail and for Evans' types IV and V with the SHS, cancellous bone around the lag screw is susceptible to yielding, thus indicating a risk of cut‐out. The volume of bone susceptible to yielding increases with an increase in size of the medial fragment. Conversely, Evans' type IV with a Gamma nail was not predicted to cut out. Our findings suggest that future clinical trials investigating fixation of unstable proximal fractures should include the size of the medial fragment and the integrity of the greater trochanter as covariables and be powered to evaluate whether intramedullary devices are superior to SHSs for Evans' type IV fractures and inferior/equivalent for type V. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:39–45, 2014.